REVIEW OF METHODS FOR MODELING ISCHEMIC STROKE IN VIVO - Irisqulov, B.U.; Abdullaev, I.F.; Makhmudov, A.R.; Baev, A.Yu.; Sariev, A.U. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Ischemic stroke is a leading cause of permanent disability worldwide. It is accompanied by devastating long-lasting motor, sensory and cognitive deficits. Currently, there is no effective treatment for ischemic stroke except intravenous perfusion with tPA, which has a limited therapeutic window and success rate. Therefore, scientists have been developing animal models to investigate the pathophysiology behind ischemic damage and discover new therapeutic drugs and rehabilitation protocols to alleviate stroke-induced deficits in patients. Developing tests that can identify and quantify behavioral and histo-pathophysiological impairments after stroke is essential to expand the development of translational therapies. In this review, we will discuss current in vivo stroke models and examination methods to assess functional outcomes after induction of experimental stroke in laboratory animals.